Usp22 is an intracellular regulator of systemic emergency hematopoiesis - Dietlein, Nikolaus; Wang, Xi; Metz, Jonas; Disson, Olivier; Shang, Fuwei; Beyersdörffer, Celine; Correa, Esther Rodríguez; Lipka, Daniel; Begus-Nahrmann, Yvonne; Kosinsky, Robyn Laura; Johnsen, Steven A.; Lecuit, Marc; et al. (Science immunology, 2022)
Emergency hematopoiesis is a concerted response aimed toward enhanced protection from infection, involving multiple cell types and developmental stages across the immune system. Despite its importance, the underlying molecular regulation remains poorly understood. The deubiquitinase USP22 regulates the levels of monoubiquitinated histone H2B (H2Bub1), which is associated with activation of interferon responses upon viral infection. Here, we show that in the absence of infection or inflammation, mice lacking Usp22 in all hematopoietic cells display profound systemic emergency hematopoiesis, evident by increased hematopoietic stem cell proliferation, myeloid bias, and extramedullary hematopoiesis. Functionally, loss of Usp22 results in elevated phagocytosis by neutrophilic granulocytes and enhanced innate protection against Listeria monocytogenes infection. At the molecular level, we found this state of emergency hematopoiesis associated with transcriptional signatures of myeloid priming, enhanced mitochondrial respiration, and innate and adaptive immunity and inflammation. Augmented expression of many inflammatory genes was linked to elevated locus-specific H2Bub1 levels. Collectively, these results demonstrate the existence of a tunable epigenetic state that promotes systemic emergency hematopoiesis in a cell-autonomous manner to enhance innate protection, identifying potential paths toward immune enhancement.